Multicultural Practice in Secondary Schools With Multicultural Background - Wedikandage, Lanka Nilmini Priyadarshani (Cultural and religious studies, 2021)
In Sri Lanka, after 30 years of civil war, multicultural education is being seen as important to help change students’ attitudes towards different ethnic and religious groups. Therefore, the major aim of this study was to investigate the views of students and staff about the multicultural policies and practices in Sinhala-medium secondary schools with multicultural background. The sample of the study comprised of 321 students, 116 teachers and five principals from five Sinhala-medium schools. In addition, four education policy-makers also contributed to the study. The key findings indicated that the majority of Sinhala and Tamil students were engaged in the school activities but Muslim students less so. In addition, all five schools had a variety of extra-curricular activities that were designed for minority ethnic groups. This is a good example for other multicultural schools in Sri Lanka. Research findings show that overall the majority of teachers suggested that they wanted some training about multicultural education. Most students were satisfied that their teachers know some expressions in the language of different students. However, teachers in these multicultural schools wanted language training to build a good intercultural relationship between teachers and students. Counsellors and teachers did not have the knowledge and skills required to provide cross-cultural counselling. Therefore, both teachers and counsellors need proper training. The research makes clear how extra/co-curricular activities are important to promote social cohesion in Sri Lanka